2x + 4(x - 1) = 2 + 4x
2x + 4x - 4 = 2 + 4x
6x - 4 = 2 + 4x
6x - 4x = 2 + 4
2x = 6
x = 3........there is 1 solution
25 - x = 15 - (3x + 10)
25 - x = 15 - 3x - 10
25 - x = -3x + 5
3x - x = 5 - 25
2x = - 20
x = -20/2
x = -10.....there is 1 solution
4x = 2x + 2x + 5(x - x)
4x = 4x + 5x - 5x
4x = 4x......this has infinite solutions
learn this...
if ur equation ends in a variable equaling a number, then there is one solution.
if ur equation ends in something not equal, like 2 = 4, or 4 = 6, then there is 0 solutions.
if ur equation ends in something equal to something,(the same) like 2 = 2, or 4x = 4x, then there is infinite solutions
Answer:
A, B, F
Step-by-step explanation:
2/3 - x + 1/6 = 6x
Collect like terms
2/3 + 1/6 = 6x + x
(4+1) / 6 = 7x
5/6 = 7x
x = 5/6 ÷ 7
= 5/6 × 1/7
x = 5/42
a) 4 - 6x + 1 = 36x
4 + 1 = 36x + 6x
5 = 42x
x = 5/42
Equivalent to the last step of the simplification above
b) 5/6 - x = 6x
5/6 = 6x + x
5/6 = 7x
This is equivalent to the third step of the simplification
c) 4 - x + 1 = 6x
4 + 1 = 6x + x
5 = 7x
x = 5/7
Not equivalent to any of the steps in the simplification above
d) 5/6 + x = 6x
5/6 = 6x - x
5/6 = 5x
x = 5/6 ÷ 5
= 5/6 × 1/5
x = 5/30
Not equivalent to any of the steps in the simplification above
e) 5 = 30x
x = 5/30
Not equivalent to any of the steps in the simplification above
f) 5 = 42x
x = 5/42
Equivalent to the last step of the simplification above
Answer:
Step-by-step explanation:
To find equivalent fractions, we multiply the numerator and the denominator by the same number, so we need to multiply the denominator of 7 by a number that will give us 21. Since 3 multiplied by 7 gives us 21, we can find an equivalent fraction by multiplying both the numerator and denominator by 3.Oct 4, 2021
Answer:
Segment AD is 4 units long, while segment BC is 5 units long. If this figure was a parallelogram, these two segments would be equal to each other.
Step-by-step explanation: